Posisi Perempuan Sebagai Wali Nikah: Metode Istinbath Hukum Khoiruddin Nasution - Amirudin Nur Muhammad; Rohmah Maulidia (Institut Agama Islam Negeri Ponorogo, 2023)
The position of a woman in marriage must obtain the approval of a guardian, namely her father or half-father. This research results from library research using descriptive analysis method and utilizing Khoiruddin Nasution's Holistic Thematic legal istinbath method. The purpose of this study is to analyze how the law of women as guardians of marriage according to Khoiruddin Nasution, what is the method of legal istinbath regarding women as guardians of marriage according to Khoiruddin Nasution, how is the relevance of thinking about women as guardians of marriage according to Khoiruddin Nasution in Indonesia. The results of this study indicate that women can become guardians. This opinion is based on the verses of the Qur'an and Hadith, which are the concepts of the rights of guardians of marriage and the rights of those close to the prospective bride and groom. Then the guardian of marriage can be male or female. Second, Khoiruddin uses the epistemological foundation of bilateral society by using a holistic thematic approach based on the bilateral paradigm and using developed sociological analysis. Third, following the development of the modern era, which is synonymous with advances in knowledge and technology that open up opportunities for women to play a role in the domestic and public sectors, Khoiruddin's thoughts about women as marriage guardians can be an alternative in the context of developing guardianship in Islamic law for this modern era.